Uterine Corpus Endometrial Carcinoma in Young Women - Caesar Muhammad Wijaya; Antonius, Puja Agung; Syamel Muhammad; Anugrah, Mutia Paramadita (Fakultas Kedokteran Universitas Andalas, 2025)
Introduction : Endometrial carcinoma is a malignant epithelial tumor that forms in the uterus's inner lining, or endometrium. The average age at diagnosis is 61 years, with cases diagnosed after 50 years more than 90%. Endometrial carcinoma is rare in young women, usually defined as occurring under age 50 or menopause, with rare cases occurring under age 40. Case Report : A 35-year-old woman nulliparous complaints of abdominal pain since 3 months ago and complained of weight loss. Based on the anamnesis, the patient is not married. On physical examination, revealed an area of firmness in the suprapubic region associated with pain on palpation. On ultrasound examination, the uterus was found to be anteflexed, with an inhomogeneous appearance, and a solid cystic mass along the uterus. Adnexa measuring 10.02 x 10.20 x 12.02 cm, vascular scale 4, not clearly defined. The patient was diagnosed with suspected uterine corpus carcinoma. Result : In this patient, a total hysterectomy and bilateral salpingo-oophorectomy were performed because the patient did not want fertility. Conclussion : In young women who want to preserve fertility, conservative management is often implemented. But, when fertility-sparing treatment is not considered, the rate of recurrence and progression is considerably low in this case. Ultimately, although fertility-sparing treatments are an attractive alternative to surgery resulting in permanent loss of fertility, unfortunately, they can only be applied in a subset of cases. The standard surgical procedure recommended is a total extra-fascial hysterectomy with bilateral salpingo-oophorectomy. Keywords: Uterine Corpus Endometrial Carcinoma, Young Women